Fire and memory : on architecture and energy - Fernández-Galiano, Luis. (Cambridge, Mass. : MIT Press, 2000)
"In Fire and Memory, Luis Fernandez-Galiano reconstructs the historical, theoretical, and contemporary relationship between architecture and energy, calling on disciplines as diverse as anthropology and economics, and in particular on ecology and thermodynamics. Beginning with the mythical fire at the origins of architecture and moving to its symbolic representation in the twentieth century, Galiano develops a theoretical dialogue between combustion and construction that ranges from Vitruvius to Le Corbusier, from the mechanical and organic to time and entropy.
Galiano points out that energy, so important to the origins of architectural theory in Vitruvius's time, has been absent from such theory since the introduction of the "dictatorship of the eye" over the other senses. With Fire and Memory, he reintroduces energy to the discussion of architecture and reminds us that the sense of touch is as necessary to an understanding of the environment as the sense of sight."--Jacket.
5. Organisms and mechanisms, metaphors of architecture: mechanical, thermal and cybernetic machines versus the living and the built : On the fraternity between buildings, living beings, and machines ; Mechanical organisms: from the bête machine to the automaton ; From the clock to the steam machine: thermodynamic Freud ; From the engine to the servomechanism: a cybernetic anthropology ; Organic mechanisms: mechanical machines and mechanizing machines ; Living machines: between the golem and the cultural fact ; Mechanical Wright, organic Le Corbusier: the biotechnical unanimity ; Mechanical cathedrals: the functional machine and the symbolic machine ; Environment and form: between tabula rasa and the memory of place -- 6. Energy as the currency of nature: a genealogy: from social energetics to the construction o fan ecological economy : Energy accounting, from myth to tool ; The prehistory of calculation: physiocrats and the tableau oeconomique ; Energy equivalences, from Rumford to Joule: energy, currency of physics ; Awareness of scarcity and waste in Jevon's Coal question ; The heyday of energy theories, from Rankine to Ostwald ; Between physical and biological economics: Geddes and the "vital budget" ; Social energetics, from Soddy to Mumford ; Energy flows in the ecosystem, between Lotka and Lindeman ; Toward an ecological economy: Georgescu's entropy and Odum's power -- Thermal space in architecture: construction and combustion, from Vitruvius to Le Corbusier ; The silent place and the silent hearth: from primitive fire to thermal muteness ; From the central hearth and the brazier to the chimney: thermal comfort and private space ; Smoke doctors and glass doctors: fireplaces, stoves, greenhouses ; Panopticon or panthermicon: homogenization and quantification ; Prisons and parliaments: practical developments and theoretical contributions ; Visual homogeneity, thermal homogeneity: the age of the tube and the exile of fire ; Functional neutrality and symbolic eloquence: thermal space in Wright and Le Corbusier ; The cultural crossroads: excess and entropy.
Includes bibliographical references (pages 262-313) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Architecture and energy conservation; Solar buildings; Symbolism in architecture; Architecture et économies d'énergie.; Constructions solaires; Symbolisme en architecture; energy efficient buildings; solar buildings; ARCHITECTURE -- Sustainability & Green Design; Architecture and energy conservation; Solar buildings; Symbolism in architecture; Energiebewusstes Bauen; Art, Architecture & Applied Arts; Architecture; v -- Writings